Facile Synthesis of Conductive Metal−Organic Frameworks Nanotubes for Ultrahigh‐Performance Flexible NO Sensors. Issue 9 (5th August 2022) - Wang, Liangjie; Chen, Xin; Yi, Zhengran; Xu, Rui; Dong, Junjie; Wang, Shuai; Zhao, Yan; Liu, Yunqi
Abstract: Cu‐benzenehexathiol (Cu‐BHT) has attracted significant attention due to its record high electrical conductivity and crystal defects Cu2c . However, the nonporous structure and small specific surface area of Cu‐BHT with two‐dimensional kagome lattice invariably limit its practical application in sensing and catalysis. In this work, Cu‐BHT nanotubes (Cu‐BHT‐NTs) are designed and prepared via a facile homogeneous reaction to solve these problems. Compared with the traditional nanorod‐like structure, the Cu‐BHT‐NTs not only have a higher specific surface area but also possess a higher proportion of crystal defects (66.6%). The successfully configured DPPTT/Cu‐BHT‐NTs heterostructure organic field‐effect transistor (OFET)‐based sensor exhibits excellent sensitivity as high as 13 610%, a minimum detection limits down to 5 ppb, and exceptional selectivity to nitric oxide (NO) toxic gases. Theoretical analysis systematically shows that Cu2c sites in the Cu‐BHT‐NTs increase the number of electrons transferred from the heterostructure to NO molecules, confirming that the high sensitivity and selectivity result from the high binding between Cu‐BHT‐NTs and NO molecules. Furthermore, a fully flexible device based on the heterojunction OFET sensor is prepared to ensure the convenience of wearing and carrying gas sensors, opening up a new avenue for the next generation of wearable intelligent electronics. Abstract : A simple and eco‐friendly approach is proposed to prepare Cu‐BHT nanotubes (Cu‐BHT‐NTs) with a high specific surface area and a large proportion of Cu2c, offering more active sites to detect NO gas. This endows that the DPPTT/Cu‐BHT‐NTs heterostructure sensor has excellent selectivity and sensitivity. Furthermore, a fully flexible sensor is successfully fabricated to demonstrate its potential application in wearable electronics.